2021
DOI: 10.1089/ast.2020.2422
|View full text |Cite
|
Sign up to set email alerts
|

UV Transmission in Natural Waters on Prebiotic Earth

Abstract: Ultraviolet (UV) light plays a key role in surficial theories of the origin of life, and numerous studies have focused on constraining the atmospheric transmission of UV radiation on early Earth. However, the UV transmission of the natural waters in which origins-of-life chemistry (prebiotic chemistry) is postulated to have occurred is poorly constrained. In this work, we combine laboratory and literature-derived absorption spectra of potential aqueous-phase prebiotic UV absorbers with literature estimates of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 130 publications
0
26
0
Order By: Relevance
“…Such fluctuations translate into either higher error rates in the interaction of early replicators, higher mutation rates, or both. For example, in an analysis of UV transmission in a prebiotic setting, the conclusions of Ranjan et al are unambiguous: insofar as prebiotic chemistries are shown to be affected by UV irradiation, they must be demonstrated to either invoke a UV-shielded milieu or be so productive as to outpace UV degradation [87]. TFT's success however notably relies on being placed in an environment where interactions are reliable-that is, where no "mistakes" are made by the players.…”
Section: Simulation Design and Methodsmentioning
confidence: 99%
“…Such fluctuations translate into either higher error rates in the interaction of early replicators, higher mutation rates, or both. For example, in an analysis of UV transmission in a prebiotic setting, the conclusions of Ranjan et al are unambiguous: insofar as prebiotic chemistries are shown to be affected by UV irradiation, they must be demonstrated to either invoke a UV-shielded milieu or be so productive as to outpace UV degradation [87]. TFT's success however notably relies on being placed in an environment where interactions are reliable-that is, where no "mistakes" are made by the players.…”
Section: Simulation Design and Methodsmentioning
confidence: 99%
“…Seawater was prepared as in the study by Marcos et al with 400 mM NaCl, 20 mM MgSO 4 , 20 mM MgCl 2 , 10 mM CaCl 2 , 10 mM KCl, 2 mM NaHCO 3 , and 1.7 mM KBr at pH 8.0. The carbonate lake conditions were adapted from Toner and Catling and Ranjan et al and included 0.1 M NaH 2 PO 4 , 10 mM KBr, 1.0 M Na 2 SO 4 , 0.24 mM Na 2 SO 3 , 10 mM lithium acetoacetate, 1.0 M H 3 BO 3 , 3.0 M NaCl, 10 mM CaCO 3 , 10 mM CaCl 2 , 2.2 mM Na 2 SiO 3 , 100 mM NaHCO 3 , 7.0 mM Na 2 CO 3 , 7.0 mM NaNO 3 , 0.6 mM KI, and 0.2 mM Na 2 SO 3 at pH 9.0. The ferrous lake conditions were adapted from Ranjan et al and Hao et al and included 0.1 mM K 4 [Fe­(CN) 6 ], 0.15 mM KBr, 0.021 mM Na 2 SO 4 , 0.2 mM NaCl, 0.23 mM CaCO 3 , 0.19 mM MgCl 2 , 0.19 mM Na 2 SiO 3 , 1.0 mM NaHCO 3 , and 100 nM Na 2 CO 3 at pH 6.3.…”
Section: Methodsmentioning
confidence: 99%
“…The carbonate lake conditions were adapted from Toner and Catling and Ranjan et al and included 0.1 M NaH 2 PO 4 , 10 mM KBr, 1.0 M Na 2 SO 4 , 0.24 mM Na 2 SO 3 , 10 mM lithium acetoacetate, 1.0 M H 3 BO 3 , 3.0 M NaCl, 10 mM CaCO 3 , 10 mM CaCl 2 , 2.2 mM Na 2 SiO 3 , 100 mM NaHCO 3 , 7.0 mM Na 2 CO 3 , 7.0 mM NaNO 3 , 0.6 mM KI, and 0.2 mM Na 2 SO 3 at pH 9.0. The ferrous lake conditions were adapted from Ranjan et al and Hao et al and included 0.1 mM K 4 [Fe­(CN) 6 ], 0.15 mM KBr, 0.021 mM Na 2 SO 4 , 0.2 mM NaCl, 0.23 mM CaCO 3 , 0.19 mM MgCl 2 , 0.19 mM Na 2 SiO 3 , 1.0 mM NaHCO 3 , and 100 nM Na 2 CO 3 at pH 6.3. For the heat degradation experiments, 200 μL of 5 mM peptide solution was placed in glass vials that were preheated at 150 °C in a Corning LSE digital dry bath heater and incubated.…”
Section: Methodsmentioning
confidence: 99%
“…However, many bystander species may attenuate the transmission of UV light in geochemically realistic complex aqueous solutions. Ranjan et al [88] found that Fe-containing species in e.g., ferrocyanide lakes are efficient at attenuating UV transmission, diminishing the potential for UV-driven constructive organic synthesis, but similarly slowing UV-driven degradation of other molecules that may go on to accumulate and constructively interact along different paths, e.g., meteoritic nucleobases [89].…”
Section: Implementing Interference Chemistrymentioning
confidence: 99%